DEVELOPMENT OF GRAPH-BASED CYBER COUNSELING MODEL WITH WEB-BASED APPLICATION PLATFORM - Pamuji, Agus; Muzaki, Muzaki; Julaeha, Eha (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2022)
Recently, almost everyone interacts with screen-focused technology. One of the forms of interaction with information technology is the use of smartphones.  Smartphone is an object that is always close to someone.   Due to this technology use, the application of counseling is increasing  when it is associated with certain needs. counseling was once conducted in traditional way for quite long time. However, it is now mostly done virtually.   Besides being able to be implemented in a remote context, counseling with a virtual platform is easier, more flexible, and can be done anywhere. The weakness that exists in virtual counseling is that it tends to be uncontrolled when viewed from the interaction pattern. Thus, the purpose of this study is to describe the pattern of interaction between counselors and counselees in virtual counseling services. The virtual counseling is run on a web application platform. The flow of communication and interaction is described by lines as segments. The final result shows that the interaction in cyber counseling services is relatively high. Another finding is the reaction made by the counselees that can successfully be identified, namely the counselee who is open and closed when expressing their problems to the counselor. Thus, the graph-based cyber counseling development model can predict which clients are open and closed.Keywords: Development, Counselling model, Cyber Counselling, Graph-Counselling